Level of Knowledge and Extent of Adoption of Farmers on Recommended Tuberose Production Practices - Roy, Shubhadeep; Bhagat, Rekha (Indian Journal of Extension Education, 2012)
The study was conducted in Nadia district of West Bengal with 80 tuberose growers to measure the level of knowledge and extent of adoption of the recommended tuberose production practices among the farmers. Most of the respondents were found to belong to medium level of knowledge and adoption category. Knowledge level and extent of adoption had shown some significant correlations with extension agency contact and mass media exposure, From the study it was clear that extension agencies have to be more active to enhance the knowledge level and extent of adoption of the flower growers.
Keywords: Level of knowledge; Extent of adoption; Recommended production practices; Risk orientation; Economic-motivation